Іменем Шевченка, в ім'я Шевченка - Жулинський, М. (Слово і Час, 2013)
Ідеться про роботу Комітету з Національної премії України імені Тараса Шевченка у 2009 –
2010 рр. Автор розповідає про лауреатів 2009 – 2010 рр., про вручення премій 2010 р., міркує
про потребу гідного відзначення 200-ліття від дня народження митця. Наведено тексти промов
із нагоди річниць Шевченка. The paper deals with the activities of the Shevchenko National Prize Committee during 2009-10.
The author acquaints the reader with the prize-winners of the years 2009 and 2010, informs on the
presentation of the award, and ponders over a worthy celebration of the writer’s 200th anniversary. The
article is supplemented with orations delivered on the occasion of various Shevchenko’s anniversaries. В статье идет речь о работе Комитета по Национальной
премии Украины имени Тараса Шевченко в 2009 – 2010 гг.
Автор рассказывает о лауреатах 2009 – 2010 гг.,
о вручении премий 2010 г., размышляет о необходимости
достойно отметить 200-летие со дня рождения поэта.
Приведены тексты выступлений, посвященных
годовщинам Шевченко.